Gambaran Kadar Hemoglobin pada Remaja Putri SMA Negeri 5 Palangka Raya: Description of Hemoglobin Levels in Female Adolescent at SMA Negeri 5 Palangka Raya City - Hidayani, Al; Ardina, Rinny; Astuti, Mia Fauzia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Female adolescents are prone to having subnormal hemoglobin levels due to the natural reduction in blood volume during menstruation. This study aimed to determine the hemoglobin levels of female students at SMA Negeri 5 Palangka Raya. A descriptive method was employed, using Point-of-Care Testing (POCT) to measure hemoglobin levels. Based on the hemoglobin test results of 95 respondents, it can be concluded that 54.7% of female students in grade 11 at SMA Negeri 5 Palangka Raya were not anemic, 23.1% were mildly anemic, 21.1% were moderately anemic, and 1.1% were severely anemic.